Relationship between workload and nurse performance at the Rawamangun Special Surgery Hospital in 2021: Hubungan Beban Kerja Dengan Kinerja Perawat di RS Khusus Bedah Rawamangun Tahun 2021 - Siti Juhairiyah; Deasy Febriyanty; Mayumi Nitami; Erlina Puspitaloka (Universitas Widya Gama Mahakam Samarinda, 2021)
Nurse performance is a measure of success in achieving nursing service goals. Good and bad performance is also influenced by workload, high workload will adversely affect the performance of nurses, poor performance of nurses will affect careers, rewards, no promotion system, and no punishment for poor performance. Based on data from the Ministry of Health of the Republic of Indonesia in 2015, the highest number of health workers was nurses as many as 147,264 people (45.65%). In Indonesia, professional nurses only make up 2% of the total existing nurses. This figure is much lower than the Philippines, which has reached 40% with one and two strata education. This study aims to determine the relationship between workload and nurse performance at the Rawamangun Special Surgery Hospital in 2021. This study uses a Cross Sectional design. The sampling method used was Total Sampling with a total sample of 30 respondents. Data analysis in this study is univariate analysis and bivariate analysis with Chi Square test. The results of the univariate analysis showed the highest proportion of good performance was 53.3%, and the highest proportion of light workloads was 63.3%. The results of the bivariate analysis showed that PR = 0.96; 95% CI = 0.430 – 2.141. There is no relationship between workload and nurse performance at the Rawamangun Special Surgery Hospital in 2021